Effect Of Using Padlet Application Toward Learning Motivation Writing Descriptive Text On The Eleventh Grade Of SMAN 7 Mandau - Andelina, Suci (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2024)
The purpose of this study was to determine the significant effect of using Padlets in writing descriptive texts. This research is using experimental method. The research will be conducted in schools at SMAN 7 Mandau. The population in this study was class XI SMAN 7 Mandau. The samples used in this study were students of class XI IPS 1 which consisted of 31 students as experimental class and students of class XI IPS 2 which consisted of 33 students as the control class. Data collection techniques used are tests, questionnaires and documentation. Checking validity of the data using statistical analysis techniques. The result showed that the result obtained from the post test showed that in the experimental class, which was original only 12 students (50%) who scored more than KKM to 21 students (88%). Meanwhile, in the control class, which was originally 13 students (54%) who scored more than the KKM, it became 17 students (71%). So, it can be concluded that there is significant effect of using the Padlet application on the motivation to learn to write descriptive texts for class XI students of SMAN 7 Mandau. Based on the results of hypothesis testing , the value of sig. (2-tailed) is 0.007 which means more less than 0.05 so Ho is rejected and Ha is accepted.